Evaluating The Tourism Supply Chain Performance in Wukirsari Cultural Village, Yogyakarta: An Importance-Performance Analysis - Kusmantini, Titik; Chen, Jau-Rong; Soegiharto, Meilan; Diantoro, Aris Kusumo; Sugandini, Dyah; Nabila, Salsabila Lintang (RSF Conference Series: Business, Management and Social Sciences, 2025)
Tourism villages play a vital role in Indonesia’s sustainable tourism strategy by combining cultural preservation with local economic empowerment. Wukirsari Cultural Village in Bantul, Yogyakarta, is a well-known destination for its batik-making heritage and cultural attractions, but its competitiveness depends on the effectiveness of the tourism supply chain (TSC). This study evaluates the TSC performance of Wukirsari using the Importance-Performance Analysis (IPA) method. Primary data were collected through structured questionnaires distributed to visitors, while secondary data were obtained from official reports and statistics. The analysis shows that attractions scored the highest importance (mean = 4.54) with strong performance (mean = 4.09), highlighting batik workshops and cultural performances as the village’s key strength. Conversely, infrastructure received the highest importance (mean = 4.57) but the lowest performance (mean = 3.83), revealing significant service gaps in sanitation facilities, water and electricity supply, and parking. Transportation, accommodation, and tour operator services were also found to underperform relative to visitor expectations, while culinary and shopping facilities performed moderately well. These findings indicate that while Wukirsari’s cultural authenticity is its primary competitive advantage, improvements in infrastructure and supporting services are urgently required. The study contributes practical recommendations for policymakers, village managers, and local SMEs to prioritize infrastructure development, maintain cultural authenticity, and strengthen stakeholder collaboration for sustainable tourism.